Rancang Bangun Prototype Pelacak Lokasi Dan Pemutus Arus Listrik Sepeda Motor Jarak Jauh Berbasis Website - Fahmi, Khairul; Saragih, Agus Sehatman; Widiatry, Widiatry (Universitas Palangka Raya, 2023)
Motorized vehicles are an important part of the daily life of the Indonesian people. The number of motor vehicle users is increasing every year, making the crime rate of the loss of a motorcycle a news that is often heard in the community. To prevent loss, a security is needed that does not only rely on handlebar locks and padlocks on motorcycles. Based on these problems, a security system is needed that can track the location of the motorcycle using the Global Positioning System (GPS) and turn off the electric current of the motorcycle over long distances that can be monitored by users through the website. This research uses a waterfall method developed based on research needs. In the design of the hardware system used by the Arduino UNO microcontroller as a system control, the SIM808 module as a network and GPS intermediary, and the relay as an electric circuit breaker. Based on the research that has been carried out, it was concluded that the system can read the location point of the motorcycle and can decide the remote electric current that is monitored through the website. Where data transfer uses GPRS communication with HTTP protocol.